Efficacy of the Aththipazha Choornam in the Management of "Perumpadu" at Siddha Teaching Hospital, Kaithady -An observational case study - Sailajah, S.; Miraaj, R. (Charithra malika kerala historical and educational cultural research museum, 2024)
According to modern aspect of perumpadu is correlated to menorrhagia. The World Health Organization reported that 18 million women aged 30 to 50 years perceived their menstrual bleeding to be extreme. Various parts of plant like bark, leaves, tender shoots, fruits, seeds and latex are medicinally important. Rise figs eaten and unripe fruits boiled and used for vegetable preparation. Aththippalam ( Ficus resemosa Lin ) is one of the fruit and good medication for excessive appetite as well as nutritional supplement. It is mentioned in all ancient scriptures of Siddha, Ayuveda, Unani and Homeopathy for the treatment of the perumpadu. The aim of the study was to evaluate the efficacy of the Aththippala chooram in the treatment of the perumpadu. This is an observational case study which was conducted in 10 diagnosed perumpadu subjects( aged between 30 to 45 with the symptoms of heavy bleeding lower abdominal pain, back ache, passing clot) who are attending the outpatient department (OPD) at Siddha Teaching Hospital, Kaithady from October to December 2023. Prepared questionnaire was used to record the data for the progress of the symptoms of perumpadu after the on e week treatment. Heavy bleeding in all selected patients, 50% had passing clots, 80% had backache and 40% had abdominal pain. After treatment, all selected patients (100%) were completely cured from backache and passing clots. Out of 8 patients (80%) and 9 patients (90%) were relief from excessive bleeding and abdominal pain respectively. According to the scientific reports, the fruit of Ficus resemosa Lin possess astringent, Anti-inflammatory, stomachic, carminative, and tonic actions, and also which is contain phytochemicals of sterols, triterpenoids, flavonoids, glycosides, tannins, carbohydrates. As well as phytonutrients are Fibre, protein, fat, Mineral, carbohydrate, Carotene, Ascorbic acid, Calcium, Phosphorus, Iron, Sulphur, Magnesium, Sodium, Potassium, Chlorine, Phosphorus, Aluminium, Manganese, Copper. Therefore, “Athippala chooranum” was effective in the treatment of perumpadu due to these pharmacological actions and phytonutrients corrected the anaemia and nutritional defecancies.
Keywords: Siddha medicine; Perumpadu; Menorregia; Aththippala chooranum; Ficus resemosa. Linn